PENGARUH KESADARAN DAN PENGETAHUAN TERHADAP KEMAUAN WAJIB PAJAK ORANG PRIBADI UNTUK MEMBAYAR PPH: (STUDI KASUS DI KABUPATEN BANTUL) - Sulastiningsih Sulastiningsih; Uriyanik Senko Prasanti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2014)
This study examines the influence of the awareness and comprehension of taxpayers who have own Tax ID (NPWP) on the willingness to pay income tax. The number of sample in this study consists of 100 taxpayers. This study also uses questionnaires in the data gathering. Validity tests of independent and dependent variables are valid and reliable with Cronbach’s Alpha greather than 0,6. Using regression analysis, this study concludes that there is a significant influence of the awareness to pay taxes and the comprehension of tax regulation on the willingness to pay taxes. Coefficient of determination shows that the models of emplamation power have significantly at 21,8%